Impact of the talent development environment on the wellbeing and burnout of Carribean youth track and field athletes - Thomas, C. E.; Gastin, P. B.; Abbott, G.; Main, L. C. (European Journal of Sport Science, 2021)
This study examined the perceived talent development environment (TDE) of youth track and field athletes within the Caribbean region and explores the relationship with their subjective wellbeing and burnout levels. A sample of 400 Caribbean youth track and field athletes (male = 198, and female = 202; age 13 to 20 years) participated in this cross-sectional study. Athletes responded to a survey which included the Talent Development Environment Questionnaire (TDEQ-5), the World Health Organization Wellbeing Index (WHO-5) and the Athlete Burnout Questionnaire (ABQ). Structural equation modelling showed that a positive and supportive TDE was associated with better athlete wellbeing and lower athlete burnout. Moreover, gender and hours of training moderated relationships of athletes` perceptions of their development environment with wellbeing and burnout levels respectively. Furthermore, there was a positive association between the support network and athlete wellbeing, while holistic quality preparation was negatively associated with athlete burnout. Development environments perceived as supportive and geared towards a holistic athlete-centred approach were associated with better athlete wellbeing and lower burnout.